The Effect of Listen-Read-Discuss (LRD) Strategy on Students' Reading Comprehension of Recount Text: A Pre-Experimental Study at Junior High School - Grecy Grecy; Eusabinus Bunau; Clarry Sada (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to investigate the effect of the Listen-Read-Discuss (LRD) strategy on eighth-grade students' reading comprehension of recount text. Despite the importance of reading comprehension in English language learning, many junior high school students still struggle with understanding recount texts, particularly in identifying main ideas, detail information, and vocabulary. This study employed a pre-experimental design with one-group pretest-posttest involving 26 students of class VIII-A at SMP St. Fransiskus Asisi Pontianak. Data were collected through pre-test and post-test using 20 multiple-choice questions targeting three aspects of reading comprehension: main idea, detail information, and vocabulary. Statistical analysis using paired t-test revealed a significant increase in students' reading comprehension scores (t = 8.40, df = 25, p < 0.05). The mean score increased from 56.53 (pre-test) to 70.57 (post-test), with an improvement of 14.04 points. Furthermore, the effect size calculation yielded ES = 1.42, indicating a strong effect. These findings demonstrate that the LRD strategy significantly enhances students' reading comprehension of recount text through its sequential phases of listening, reading, and discussing, which build prior knowledge and promote collaborative learning.